An insight into antagonist binding and induced conformational dynamics of class B GPCR corticotropin-releasing factor receptor 11. Issue 7 (16th July 2015) - Xu, Junli; Wang, Zhonghua; Liu, Pi; Li, Dongmei; Lin, Jianping
<x xml:space="preserve">Abstract</x> The binding of small-molecule antagonists, CP-376395 and MTIP, would induce conformational dynamics behaviors of CRF1R.